Synthesis and photodiode properties of chalcone substituted metallo-phthalocyanine - GÖRGÜLÜ, AHMET ORHAN (My University, 2020)
In this study, we aimed to investigate the photodiode properties of the chalcone substituted-phthalocyanine complex due to the important physical properties of the phthalocyanine and chalcone compounds. For this purpose, in the first step, a heterocyclic chalcone compound (HC) bearing a pyridine and hydroxyl group was obtained from the reaction of 4′-hydroxyacetophenone with pyridine-3-aldehyde. In the second step, the chalcone-substituted phthalonitrile compound (HCA) was obtained by interacted 4-nitroftalonitrile with the compound HC in the presence of K2CO3 in DMF in an argon atmosphere. The new chalcone substituted metallo-phthalocyanine (HCA-Co) was synthesized from the reaction of compound HCA with Co (II) acetate according to heating of solid phase method under an inert atmosphere. The structure of HC and HCA-Co were fully characterized by using 1H, and 13C-APT NMR, FT-IR, elemental analysis, UV–Vis spectroscopy. The HCP-Co thin-film planar heterojunction diode was prepared. The organic layer was deposited onto the p-Si substrate to obtain an Al/p-si/phthalocyanine(HCP-Co)/Al diode. The current (I)- voltage (V) characteristics of heterojunction diode was measured under dark and illuminated conditions (20–100 mW/cm2) at room temperature. The electrical characteristics of the device were measured. The ideal factor value was found to be 5.20 and according to this value, the diode exhibits non-ideal behavior. The frequency dependence of capacitance and the role of interface states were examined. The results showed that chalcone substituted metallo-phthalocyanine has a photodiode and photocapacitor characteristic. Therefore, chalcone-linked metallo-phthalocyanine can be applied in solar tracking systems.
Keywords: Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; KİMYA, ANALİTİK; SPEKTROSKOPİ; KİMYA, ORGANİK; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; CHEMISTRY, ORGANIC; Fizik Bilimleri; Organik Kimya; İnorganik kimya; Physical Sciences; Organic Chemistry; Chalcone; Photo-physical; Photodiode; Phthalocyanine; Synthesis